Navigating trade policy shocks - Meng, Ning,Wang, Feicheng (CESifo, 2023)
This paper explores an under-researched margin of firms' export adjustments in response to negative trade policy shocks: export reallocation across markets. Using detailed Chinese customs data spanning from 2000 to 2015 and a difference-in-differences approach, we compare export dynamics between multi-destination exporters that were subject to antidumping (AD) duties and those that were not affected. Our empirical results show that, on average, AD duties reduced firms' entry into new markets and increased their exit from existing markets. These effects were less pronounced for exports to high-income destinations and high-quality products. Continuing exporters, however, raised their exports to non-AD markets after being affected by AD duties and this effect was stronger for high-income destination exports. Further analysis underscores the role of quality upgrading in explaining the trade-promoting effect of AD duties in third countries. Our findings reconcile the seemingly contradictory trade diversion and tariff echoing effects of AD duties documented in earlier studies.
10419/282440
Keywords: Graue Literatur; antidumping; multi-destination firms; within-firm adjustment; quality